2015
DOI: 10.1111/ecca.12167
|View full text |Cite
|
Sign up to set email alerts
|

A General Equilibrium Analysis of Personal Bankruptcy Law

Abstract: We analyse an economy where principals and agents match and contract subject to moral hazard. Bankruptcy law defines the limited liability constraint in these contracts. We analyse Walrasian allocations to generate the following predictions: (i) weakening bankruptcy law causes redistribution of debt and welfare from poor agents and principals to rich agents; (ii) exemption limits Pareto‐dominate other bankruptcy laws if project size is fixed; (iii) means‐testing (as in recent US personal bankruptcy law) that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Above all the following papers, the most relevant to the current paper is [3], which examines a many-to-one two-sided matching model of lenders and borrowers in the context of a principal-agent contracting problem. They use the theoretical model to examine the general equilibrium effects of changes in the limited liability constraint due to new bankruptcy laws.…”
Section: Related Literature and Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Above all the following papers, the most relevant to the current paper is [3], which examines a many-to-one two-sided matching model of lenders and borrowers in the context of a principal-agent contracting problem. They use the theoretical model to examine the general equilibrium effects of changes in the limited liability constraint due to new bankruptcy laws.…”
Section: Related Literature and Contributionmentioning
confidence: 99%
“…Additionally, the coexistence of different types of contracts in the same market is widely documented in both the empirical and theoretical literature. However, the paucity of theoretical research examining the coexistence of exclusive and nonexclusive contracts is surprising, with [3] representing the only such work, known to this author, to obtain results on contract coexistence.…”
Section: Introductionmentioning
confidence: 97%
“…They found that filers had more limited access to unsecured credit. Lilienfeld and Toal-Mookherjee [ 24 ] showed in a two-sided matching model that changing exemption levels in bankruptcy law induced a redistribution of credit. A more lenient system resulted in that lending to poorer borrowers shrinks, while for the richest agents grew and the cost of borrowing shrank.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…One can also analyze situations where it is the agent (subject to moral hazard) who contracts with several principals. One example of such a situation is found in vonLilienfeld-Toal and Mookherjee (2016), who analyze a credit market. This paper also illustrates that an exogenous shock may have a general equilibrium effect in a market contracts which is absent in an isolated principal-agent relationship.…”
mentioning
confidence: 99%